1998
DOI: 10.1139/cjfr-28-8-1249
|View full text |Cite
|
Sign up to set email alerts
|

Radial tree-growth modelling with fuzzy regression

Abstract: A so-called fuzzy linear regression is used in dendroecology to model empirically tree growth as a function of a bioclimatic index representing the water stress, i.e., the ratio of actual evapotranspiration to potential evapotranspiration. The response function predicts tree growth as (fuzzy) intervals, narrow in the domain where the bioclimatic index is most limiting and becoming progressively larger elsewhere. The method is tested with a population of Pinus pinea L. from the Provence region in France. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…The most important environmental variables controlling the Mediterranean distribution of P. pinea have been reported to be the average temperature of the coldest month, determining plant survival, and winter precipitation, being largely responsible for growth rates (Thuiller et al, 2003a,b); the high sensitivity of growth to precipitation has also been confirmed by Boreux et al (1988) andRaventó s et al (2001). This is particularly true for the study site, where groundwater flow is reduced and water table recharge is mainly related to local precipitation (Baldini et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…The most important environmental variables controlling the Mediterranean distribution of P. pinea have been reported to be the average temperature of the coldest month, determining plant survival, and winter precipitation, being largely responsible for growth rates (Thuiller et al, 2003a,b); the high sensitivity of growth to precipitation has also been confirmed by Boreux et al (1988) andRaventó s et al (2001). This is particularly true for the study site, where groundwater flow is reduced and water table recharge is mainly related to local precipitation (Baldini et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…La construction du cerne durant l'été est donc dépendante des précipitations qui renouvellent le stock d'eau dans le sol, de l'intensité de l'évapotranspiration déterminée par les températures et des caractéristiques édaphiques du sol, notamment la réserve utile. Ce phénomène a déjà été étudié en région méditerranéenne, notamment sur Pinus pinea, avec la mise en évidence de l'influence du paramètre ETP/ETR sur les variations inter-annuelles de la croissance [5]. Nos résultats montrent, par ailleurs, que le stress hydrique serait un déclencheur de la transition bois initial-bois final.…”
Section: Discussionunclassified
“…This model has already been used in dendroecology in order to assess the influence of water stress on radial tree growth of an Italian stone pine (Pinus pinea L.) stand in south-east France (Boreux et al 1998;Gadbin-Henry 1994).…”
Section: Water Balance Modellingmentioning
confidence: 99%